A Qualitative Exploration of Challenges for International Students Enrolled in Health Professional Education Degrees in Australia - William, Scott; Peters, Kath; Hegazi, Iman (Journal of International Students, 2024)
This qualitative study reports on the experiences of international students enrolled in a Health Professional Education program at a large Australia university. International students have long contributed to Australia’s economy. However, the sustainability of international students’ contributions to Australia’s economy is questionable. Challenges for international students have been widely reported in Australia. Students enrolled in Health Professional Education having unique challenges of their own. In total, 19 semi-structured interviews were conducted in 2020 and the data were thematically analysed. The findings uncovered numerous challenges for international students and those unique to international students enrolled in health- related degrees. Although all identified challenges may not be feasible to address, this study highlights recommendations for strategies that could be implemented by universities and policy makers to reduce challenges and to enhance graduate outcomes for this student population.